The uncounted: politics of data and visibility in global health. Issue 8 (13th October 2017) - Davis, Sara L. M.
ABSTRACT: This article explores the political and economic factors that are driving shifting data in the context of HIV. In order to measure progress towards the Sustainable Development Goal (SDG) 3.3 on health, global health agencies such as UNAIDS, the Global Fund to Fight AIDS, TB and Malaria, and PEPFAR all rely on HIV data routinely reported by countries. This data is not produced in a political vacuum. Key populations vulnerable to HIV (men who have sex with men, people who inject drugs, sex workers and transgender people) are often hidden due to stigma and criminalisation. However, the absence of this data creates a paradox in which invisibility reinforces invisibility. Key population size estimates are a central tool for planning and resourcing national and global HIV programming, but these become hard to obtain when key populations are hidden and political leaders deny their existence. Pressure from health financing agencies is changing these power dynamics in some countries. Key populations who participate in these consultations question size estimates, interrogate the politics of HIV data, and demand that studies be more inclusive, ethical and attuned to their human rights. In the fight against HIV, data is a critical stake in the struggle.